Representasi Kesetiaan dalam Film Pendek “Ruang Tunggu” (Analisis Semiotika Roland Barthes) - Nasution, Ryan Efendi; Yusmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research discusses loyalty to a partner in a short film entitled Ruang Tunggu, produced by PT. Visualan Kreasi Indonesia and PT. KAI. Short films are audiovisual works with a shorter duration than feature or feature films. This short film tells the story of the loyalty of a wife who waits for her husband to return for years. This research aims to identify the meaning of denotation, connotation and myths about loyalty in the film of Ruang Tunggu. The research method used is qualitative, data collection techniques through observation and documentation. Data analysis uses Roland Barthes' semiotic approach, which emphasizes key concepts such as denotation, connotation and myth. The results of the research show that the film of Ruang Tunggu successfully represents the meaning of great loyalty from a wife. The meaning in terms of denotation, connotation and myth represents patience and steadfastness that never changes. Loyalty is represented through sharing scenes including the wife taking care of all the memories left by her husband, the wedding ring which is still wrapped around her ring finger, the ritual of looking for and waiting for her husband's return on the train platform which continues from the first day her husband does not return until he dies pick him up